Nitroso-Redox Balance and Mitochondrial Homeostasis Are Regulated bySTOX1, a Pre-Eclampsia-Associated Gene - Ludivine Doridot; Laurent Châtre; Aurélien Ducat; Jean-Luc Vilotte; Anne Lombès; Céline Méhats; Sandrine Barbaux; Rosamaria Calicchio; Miria Ricchetti; Daniel Vaiman (2014)
Storkhead box 1 (STOX1) is a winged-helix transcription factor that is implicated in the genetic forms of a high-prevalence human gestational disease, pre-eclampsia. STOX1 overexpression confers pre-eclampsia-like transcriptomic features to trophoblastic cell lines and pre-eclampsia symptoms to pregnant mice. The aim of this work was to evaluate the impact of STOX1 on free radical equilibrium and mitochondrial function, both in vitro and in vivo.Transcriptome analysis of STOX1-transgenic versus nontransgenic placentas at 16.5 days of gestation revealed alterations of mitochondria-related pathways. Placentas overexpressing STOX1 displayed altered mitochondrial mass and were severely biased toward protein nitration, indicating nitroso-redox imbalance in vivo. Trophoblast cells overexpressing STOX1 displayed an increased mitochondrial activity at 20% O2 and in hypoxia, despite reduction of the mitochondrial mass in the former. STOX1 overexpression is, therefore, associated with hyperactive mitochondria, resulting in increased free radical production. Moreover, nitric oxide (NO) production pathways were activated, resulting in peroxynitrite formation. At low oxygen pressure, STOX1 overexpression switched the free radical balance from reactive oxygen species (ROS) to reactive nitrogen species (RNS) in the placenta as well as in a trophoblast cell line.In pre-eclamptic placentas, NO interacts with ROS and generates peroxynitrite and nitrated proteins as end products. This process will deprive the maternal organism of NO, a crucial vasodilator molecule.Our data posit STOX1 as a genetic switch in the ROS/RNS balance and suggest an explanation for elevated blood pressure in pre-eclampsia.